Insect Conservation Biology 2007
DOI: 10.1079/9781845932541.0245
|View full text |Cite
|
Sign up to set email alerts
|

Insects and climate change: processes, patterns and implications for conservation.

Abstract: The effects of climatic change on insect biodiversity and conservation, and the importance of insects as model systems for biological responses to climatic change and associated conservation measures are described. Studies on recent responses of insects to climatic change (shifts in distribution and phenology) and mechanisms behind climate-related shifts in distribution and phenology (those related to population size, growth, survival, fecundity and adaptive responses, and those associated with biotic interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 162 publications
(206 reference statements)
0
46
0
1
Order By: Relevance
“…Many studies have shown that climate change causes range shifts to higher latitudes and elevations, as species expand into areas that become climatically suitable and contract from areas that become too warm (Wilson et al 2007). Additionally, climate warming affects the phenology of species leading to potential mismatches between interacting species, for example, between pollinators and plants (Stenseth & Mysterud 2002).…”
Section: Anthropogenic Influences On Tropical Forest Biodiversitymentioning
confidence: 99%
“…Many studies have shown that climate change causes range shifts to higher latitudes and elevations, as species expand into areas that become climatically suitable and contract from areas that become too warm (Wilson et al 2007). Additionally, climate warming affects the phenology of species leading to potential mismatches between interacting species, for example, between pollinators and plants (Stenseth & Mysterud 2002).…”
Section: Anthropogenic Influences On Tropical Forest Biodiversitymentioning
confidence: 99%
“…6 ), exercises that clearly endorsed that climate tolerance and suitability is essential to establishment success. However, the four general conclusions on insect conservation in a changing climate made by Wilson et al ( 2007 ) (Table 10.3 ) all raise issues of very wide concern. Not least, and as recognised widely by others, the contrast in responses between generalist and specialist taxa parallels some characteristics of 'more invasive' versus 'less invasive' species in other contexts.…”
Section: Climate Changementioning
confidence: 97%
“…Putative infl uences of global warming refl ect the widespread scenarios that temperature and precipitation are important determinants of species' regional distributions through infl uences on physiological parameters, and set limits to elevational and latitudinal ranges of many taxa (Wilson et al 2007 ). However, fi rmly establishing any such causal link between range limits and climatic factors is diffi cult: as Gaston ( 2009 ) noted, relevant evidence may take the form that conditions that exceed levels within the current range preclude completion of the normal life cycle or impose excessive mortality.…”
Section: Climate Changementioning
confidence: 99%
“…Warmer temperatures are expected to increase levels of carbon dioxide and alter precipitation on grasslands, which are likely to suffer further habitat fragmentation and loss, making it difficult for all biota to adapt (Lovejoy and Hannah 2005;Pachauri and Reisinger 2007). There is growing evidence that insects are one of the first groups of living organisms to respond to global warming (Harrington and Stork 1995;Wilson et al 2007). Hillstrom and Lindroth (2008) found that elevated CO 2 and O 3 altered the abundance of insects and composition of communities in forests, but did not affect family-level richness.…”
Section: The Vast Ocean Of Level Prairie Which Lies To the West Of Rementioning
confidence: 99%